Optimizing the duration of sensory and motor blocks and the use of substances affecting them in unilateral spinal anesthesia. (Eurasian Medical Research Periodical, 2024)
Spinal anesthesia is a frequently used method with ease of performance and high success rate in orthopedic surgery of the feet. It is widely used to provide rapid and effective sensory and motor block that alleviates the body's stress response to surgical trauma, reducing intraoperative blood loss, postoperative thromboembolism, and morbidity and mortality compared with general anesthesia [142; 1493-1499-b]. However, spinal anesthesia is the most dangerous of all regional methods [163; 21-24 p]. It, like other methods of anesthesia, is not without disadvantages. Adverse effects include hypotension, bradycardia, nausea and vomiting, postpuncture headache, and urinary retention [55; pp. 906-916]. Hypotension is the most common complication of conventional bilateral spinal anesthesia, occurring in more than 30% of patients [144; pp. 387-393].